Perencanaan dan Perancangan Pusat Industri Dan Budidaya Buah Kelapa Terpadu Di Kabupaten Jembrana - Ida Bagus Komang Kresna Adi Pratama Surya; I Wayan Parwata; Agus Kurniawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Coconut is a plant that is rich in benefits, almost all of its parts can be used as commercial goods that have a selling value ranging from stems, trees, fruit, coir, shells to the water. Jembrana Regency is one of the coconut producing areas. Jembrana Regency has the largest coconut plantation area in Bali, reaching 17,000 hectares. Behind the abundant natural resources, human resources are still not good, coconut farmers who cultivate coconuts are still not sufficient to meet their daily needs due to the loss of coconut share in Jembrana with other areas in Indonesia. regional Bali and also outside Bali, especially due to the pandemic which made demand for coconut from outside Bali experience a decline in prices and also many farmers only sell coconuts in whole form without being processed into commercial goods due to lack of knowledge and equipment that can process and produce goods. coconut processing. In the tourism sector, Jembrana tends to be quiet. Based on the problems that occurred, the Integrated Coconut Fruit Industry and Cultivation Center was proposed, a facility to process and produce processed coconut products including development, marketing, education, and cultivation. The location chosen was in Candikusuma Village, Melaya District, Jembrana Regency. With the approach of the theme "Ecology Architecture" and the concept of "Eco-Tourism Industry"